The archaeology of early medieval Poland : discoveries - hypotheses - interpretations - Buko, Andrzej, 1947- (Leiden : Brill, 2008)
This is the first academic book which concentrates on the discoveries of medieval date (6th- 13th centuries) from the territory of modern Poland. The book covers the principal research questions, such as the origins of the Slavs, societies of the proto-state period and the origins of the Polish state. The volume also includes a discussion of the most interesting, sometimes controversial, archaeological discoveries or issues. These include pagan Slavonic holy places, the monumental mounds of Little Poland, the first traces of medieval writing, exceptional strongholds, the origins of Polish towns, rural landscapes, archaeology of the oldest monastic complexes, and the question of locals and aliens viewed through archaeological evidence and many other topics. The book is meant mainly for students, archaeologists and historians. It can also be useful for a wider audience interested in the history and archaeology of central Europe. In November 2006 "The Archaeology of Early Medieval Poland" received the KLIO Award from the Association of Polish History Publishers.
1, Archaeology Of Early Medieval Poland: Beginnings Of Interest, Birth And Development -- 2, Sources And Methods -- 3, How Did The Slavs Get To Polish Lands? -- 4, Mysteries Of The Pre-State Period -- 5, Holy Mountains -- 6, Pagan Cemetery Or Holy Grove? -- 7, Monumental Mounds In Little Poland -- 8, The Earliest Medieval Script In Poland? -- 9, How Poland Came Into Being -- 10, Towns Still Under Investigation -- 11, Other Central Places -- 12, Rural Landscapes -- 13, The Earliest Monastic Complexes -- 14, The Puzzle Of The Century: Pottery Marks -- 15, Locals And Migrants -- Appendix One, Some Notes On The Translation Of Andrzej Buko’S ‘Archaeology Of Early Medieval Poland’ / Paul Barford -- Appendix Two, A Brief Guide To The Pronunciation Of Polish Words / Paul Barford
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 6.-13. století; archeologické nálezy -- Polsko; archeologické výzkumy -- Polsko; archeologie středověku -- Polsko; antiquities -- Poland; excavations (archaeology) -- Poland; medieval archaeology -- Poland; Polsko -- dějiny -- 6.-13. století; Poland -- history -- 6th-13th centuries; monografie; e-knihy online; monographs; e-books online